2019
DOI: 10.1038/s41598-019-51657-0
|View full text |Cite
|
Sign up to set email alerts
|

Fractal nature of groundwater level fluctuations affected by riparian zone vegetation water use and river stage variations

Abstract: Groundwater systems affected by various factors can exhibit complex fractal behaviors, whose reliable characterization however is not straightforward. This study explores the fractal scaling behavior of the groundwater systems affected by plant water use and river stage fluctuations in the riparian zone, using multifractal detrended fluctuation analysis (MFDFA). The multifractal spectrum based on the local Hurst exponent is used to quantify the complexity of fractal nature. Results show that the water level va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…At the same time, barometric pressure and temperature were recorded at the location We select a 1-h interval in our study to satisfy the request of wavelet analysis (equal interval), since the river stages were recorded with a 1-h interval. A detailed description of the study site can be found in the work of Zhu et al (2012) and Sun et al (2019). Precipitation is another surface factor that can affect the groundwater level, since it can provide recharge to the aquifer and river.…”
Section: Field Site and Data Collectionmentioning
confidence: 99%
“…At the same time, barometric pressure and temperature were recorded at the location We select a 1-h interval in our study to satisfy the request of wavelet analysis (equal interval), since the river stages were recorded with a 1-h interval. A detailed description of the study site can be found in the work of Zhu et al (2012) and Sun et al (2019). Precipitation is another surface factor that can affect the groundwater level, since it can provide recharge to the aquifer and river.…”
Section: Field Site and Data Collectionmentioning
confidence: 99%
“…Riparian zone, the part of the watershed immediately adjacent to the stream channel, is considered as buffer zones and gateways of nutrients and pollutants in catchments for streams (Hester & Fox, 2020; Li et al, 2020). Hydrological processes in riparian zones play an important role in the controlling of hydrogeochemical (Veizaga et al, 2019; Wen et al, 2018), biogeochemical (Ledesma et al, 2016), and ecological (Sun et al, 2019; Tai et al, 2018; Thibault et al, 2017) processes in stream‐aquifer systems. It was reported that significant riparian evaporative fluxes caused gaining river conditions to change to losing conditions and led to groundwater chemistry changes (America et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…and ecological (Sun et al, 2019;Tai et al, 2018;Thibault et al, 2017) processes in stream-aquifer systems. It was reported that significant riparian evaporative fluxes caused gaining river conditions to change to losing conditions and led to groundwater chemistry changes (America et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They identified climate variability (at interannual and decadal scales) as the prime driver of the groundwater availability. Sun et al (2019) characterized the multifractal nature of groundwater level fluctuations under the impact of vegetation.…”
Section: Introductionmentioning
confidence: 99%